Thermally stable core–shell Ni/nanorod-CeO2@SiO2 catalyst for partial oxidation of methane at high temperatures. Issue 29 (11th July 2018) - Zhu, Shaohong; Lian, Xinyi; Fan, Tingting; Chen, Zhou; Dong, Yunyun; Weng, Weizheng; Yi, Xiaodong; Fang, Weiping
Abstract : Core–shell Ni/nanorod-CeO2 @SiO2 catalyst prepared by a microemulsion method shows high catalytic activity and good thermal stability for the partial oxidation of methane. Abstract : During partial oxidation of methane (POM), the greatest challenge is to maintain the thermal stability of the catalyst at high temperatures. One of the most effective ways to improve thermal stability is to construct core–shell structure. Herein, using a microemulsion method, we synthesized a core–shell Ni/nanorod-CeO2 @SiO2 catalyst, in which the Ni nanoparticles were supported on the CeO2 nanorods and encapsulated by SiO2 shells. Based on a series of characterizations, we found that the Ni particles are of nanosize (2.2 nm) and the thickness of the SiO2 shell is about 8 nm in the core–shell catalyst. Moreover, the Ni/nanorod-CeO2 @SiO2 catalyst can perfectly maintain rod-like structures of the CeO2 support and enhance interaction between the metal Ni and CeO2, significantly reducing the sintering of metal Ni particles at high temperatures. Therefore, the as-prepared Ni/nanorod-CeO2 @SiO2 catalyst shows high catalytic activity and good thermal stability during the POM reaction.